2017
DOI: 10.1148/radiol.2017161259
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Virtual Bone Strength Testing in Osteoporosis Screening Programs for Postmenopausal Women in the United States

Abstract: Purpose To investigate whether assessment of bone strength with quantitative computed tomography (CT) in combination with dual-energy x-ray absorptiometry (DXA) is cost-effective as a screening tool for osteoporosis in postmenopausal women. Materials and Methods A state-transition microsimulation model of osteoporosis for postmenopausal women aged 55 years or older was developed with a lifetime horizon and U.S. societal perspective. All model inputs were derived from published literature. Three strategies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Our results demonstrate that BCT analysis of previously taken routine abdominal or pelvic CT is at least as effective as DXA testing in a large clinical setting. A recent cost‐effectiveness study concluded that BCT analysis, when performed on a dedicated hip CT scan (ordered specifically for BCT analysis), should be cost‐effective when the charge for the BCT analysis is set at $100 over the cost of a dedicated hip CT scan . At that pricing, ancillary BCT should be even more cost‐effective because there is no need for a dedicated hip CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that BCT analysis of previously taken routine abdominal or pelvic CT is at least as effective as DXA testing in a large clinical setting. A recent cost‐effectiveness study concluded that BCT analysis, when performed on a dedicated hip CT scan (ordered specifically for BCT analysis), should be cost‐effective when the charge for the BCT analysis is set at $100 over the cost of a dedicated hip CT scan . At that pricing, ancillary BCT should be even more cost‐effective because there is no need for a dedicated hip CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed QALY values for the no fracture state of 0.84 for women and 0.87 for men. Disutility values for the first and subsequent years after hip fracture were obtained using multipliers of 0.797 and 0.899, respectively ( Table 1 (1,5,7,10,11,17,25,26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) ). As noted above, these parameter values are conservative because we did not consider QALY gains associated with preventing any other major osteoporotic fractures (e.g.…”
Section: Participate In the Bct Program And Undergo Bct Screeningmentioning
confidence: 99%
“…BCT testing (per test performed) $100 $150-250 Agten and colleagues (25) ; Viceconti and colleagues (26)…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations